Modalitas Terapi Vitiligo pada Anak - Nathania Amelinda; Endra Yustin Ellistasari; Indah Julianto (PT Dexa Medica, 2022)
itiligo is a pigmentation disorder characterized by depigmented patches on skin and hair due to functional loss of melanocytes. Vitiligo in children is generally associated with other autoimmune diseases and has serious cosmetic and psychosocial impact. Treatment modalities for vitiligo in children consist of topical therapy, phototherapy, systemic therapy, and surgery. Vitiligo in children has a relatively good prognosis compared to adult cases. Repigmentation in childhood vitiligo usually happen spontaneously and relapses are rare.